Water Quality of Unconfined Aquifer in Universitas Negeri Malang Following the Drinking Water Quality Standard of Indonesian Ministry of Health - Utaya, Sugeng; Taryana, Didik; Mashitoh, Ferryati; Arinta, Dicky; Prasad, Ravinesh Rohit (Tunas Geografi, 2024)
Abstract                                                             The quality of groundwater is naturally determined by water-bearing rock characteristics. However, the progression of civilian activities also negatively affects the groundwater quality. Therefore, this study aims to assess groundwater's physical, chemical, and biological characteristics in Indonesia's Universitas Negeri Malang (UM) campus area and evaluate its compliance with drinking water quality standards, particularly the Class A standard. A comparative descriptive strategy was utilized in the study by involving groundwater in the campus area of UM. The focus of the research is water quality in unconfined aquifers. Through purposive sampling, 12 wells were selected to ensure appropriate spatial dispersion. Water samples were collected in sample bottles and tested for physical, biological, and chemical properties. The Perum Jasa Tirta I Malang carried out these water quality tests. Water quality data were analyzed qualitatively, descriptively, and comparatively. This study concludes that (1) the groundwater on the UM campus generally meets the physical criteria for drinking water quality standards; (2) the chemical quality of the groundwater on the UM campus still satisfies the drinking water quality standards; and (3) biologically, the free groundwater on the UM campus fails to meet drinking water quality standards. The novelty of this research is that the biggest threat to the quality of free groundwater in the campus area is bacterial contamination from sanitation activities. Accordingly, it is recommended that groundwater is boiled before being utilized for drinking water purposes to neutralize the E. coli bacteria present in all well water samples.Keywords: Water Quality of Unconfined Aquifer; The Drinking Water; Quality Standard